Parameter Optimization Of Fused Deposition Modelling Under Ambient Temperature Control - Harun, Nurul Hatiqah (2019)
Fused Deposition Modelling (FDM) is one of the most popular RP techniques available in the market. However, there is still limitation in terms of FDM performance such as surface roughness and dimensional accuracy. Creation of a part with good surface roughness and dimensional accuracy is critical as it can affect the part accuracy, post-processing cost and functionality of the parts. Based on the literature review, it was found that studies on the effect of ambient temperature in improving the surface roughness and dimensional accuracy of FDM built parts have been limited to certain extend. Environmental factors such as temperature and relative humidity have been believed to be the sources of error affecting surface finish and dimensional accuracy. Besides, temperature fluctuations during production also believed could lead to delamination and higher surface roughness. Therefore, this research study aims to investigate the effect of parameter variables such as ambient temperature, layer thickness and part angle to the samples fabricated by using FDM machine. The response surface methodology (RSM) was employed by using historical data in the experiment to determine the significant factors and their interactions on the FDM performance. Three levels manipulated factors namely ambient temperature (30°C, 45°C, 60°C), layer thickness (0.178 mm, 0.267 mm, 0.356 mm) and part angle (22.5°, 45°, 67,5°) have been studied. A total of 29 numbers of experiments had been conducted including two replications at center point. The results showed that all the parameter variables have significant effects on the part surface roughness and dimensional accuracy. Layer thickness are the most dominant factors affecting the surface roughness. Meanwhile, ambient temperature was the most dominant in determining part dimensional accuracy. The responses of various factors had been illustrated in diagnostic plot and interaction graph. Besides, the results also had been illustrated in further surface roughness and cross-sectional sample analysis. The optimum parameter required for minimum surface roughness and dimensional accuracy was at ambient temperature 30.01°C, layer thickness 0.18 mm and part angle 67.38°. The optimization has produced the maximum productivity with RaH 2.78 µm, RaV 12.38 µm and RaS 10.92 µm. Meanwhile, dimensional accuracy height 3.2%, length 2.1%, width 3.7% and angle 0.39°.